The Effect of Serum Magnesium and Calcium Levels on the Severity of Acute Ischemic Stroke in Patients Hospitalized for Less Than 7 Days - Indra Wijaya; Zulfikar Lubis; Chairil Amin Batubara (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke ranks as the second leading cause of death worldwide, with an annual mortality of approximately 5.5 million. Stroke is classified into ischemic stroke and hemorrhagic stroke, the latter including intracerebral hemorrhage and subarachnoid hemorrhage. Ischemic stroke, caused by arterial occlusion, accounts for the majority of stroke cases. This study aims to evaluate the effect of serum magnesium and calcium levels on the severity of acute ischemic stroke in patients hospitalized for less than 7 days at the Stroke Unit of Adam Malik Hospital. This study was an analytical research with a cross-sectional design, which involved measuring multiple variables at a single point in time. Data were collected from 50 patients admitted to the Stroke Unit of Adam Malik Hospital. Sampling was conducted consecutively for all patients who met the inclusion criteria. The data were analyzed using the Shapiro-Wilk test to assess the normality of the distribution. From a total of 50 study participants, the majority (54%) were male. The average age of the subjects was 58.42 years, with an age range of 29 to 80 years. Most patients had a high school education (42%). The mean NIHSS (National Institutes of Health Stroke Scale) score was 7.58, indicating a moderate level of stroke severity, with NIHSS scores ranging from 5 to 19. The average serum magnesium and calcium levels in patients with acute ischemic stroke were within normal limits, recorded at 2.01 mg/dL and 9.25 mg/dL, respectively. There was no significant association between serum magnesium and calcium levels and the severity of acute ischemic stroke based on NIHSS scores, with p-values of 0.499 and 0.504, respectively.